2016
DOI: 10.1002/ldr.2519
|View full text |Cite
|
Sign up to set email alerts
|

Seed Removal due to Overland Flow on Abandoned Slopes in the Chinese Hilly Gullied Loess Plateau Region

Abstract: Theories and empirical evidences suggest that seed removal due to overland flow can result two main spatial outcomes, seed redistribution and seed loss. However, it is not fully understood in some sensitive habitats, such as in abandoned cropland of the Chinese hilly gullied Loess Plateau region. This study evaluates seed redistribution patterns in major micro‐sites including eroded, deposited and trap micro‐sites, characterizes seed loss by using runoff plot, and explores the effect of vegetation coverage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Moreover, check dams were one of the most dominant forms of human impact on fluvial systems and had considerably reduced stream bed slope, which caused a disruption in connectivity and diminished the sediment transport capacity of the rivers (Díaz et al, 2014;Poeppl et al, 2015). Other man-made pathways (terrace embankments, roads, fish-scale pits and tracks), topographic factors, soil moisture, soil components and vegetation also had a major influence on sediment connectivity and the frequency of water and sediment fluxes (Cao et al, 2015;Li et al, 2016a;Marchamalo et al, 2016;Masselink et al, 2016;Yu et al, 2016). In general, the effect of check dams retention for sediment yield had major implication for flood control and sediment delivery into the main rivers and reservoirs downstream .…”
Section: Influence Of Check Dams On the Sediment In Downstreammentioning
confidence: 99%
“…Moreover, check dams were one of the most dominant forms of human impact on fluvial systems and had considerably reduced stream bed slope, which caused a disruption in connectivity and diminished the sediment transport capacity of the rivers (Díaz et al, 2014;Poeppl et al, 2015). Other man-made pathways (terrace embankments, roads, fish-scale pits and tracks), topographic factors, soil moisture, soil components and vegetation also had a major influence on sediment connectivity and the frequency of water and sediment fluxes (Cao et al, 2015;Li et al, 2016a;Marchamalo et al, 2016;Masselink et al, 2016;Yu et al, 2016). In general, the effect of check dams retention for sediment yield had major implication for flood control and sediment delivery into the main rivers and reservoirs downstream .…”
Section: Influence Of Check Dams On the Sediment In Downstreammentioning
confidence: 99%
“…We need better comprehension of the impact of abandonment on water resources (López-Vicente et al, 2016), soil properties (Novara et al, 2015;Brevik et al, 2016;Nadal-Romero et al, 2016) and its impact on the chemical composition of the atmosphere due to changes in the carbon cycle induced by the abandonment (Gabarrón-Galeote, 2016a;2016b;Nadal-Romero et al, 2016;Novara et al, 2016). Although land abandonment mainly occurred in developed countries during the last century and this is where most of the research has been conducted (Shelef et al, 2015), it is now also a process found in developing countries such as some regions of Ethiopia (Mekonnen et al, 2015;Tesfahunegn et al, 2016), China (Kou et al, 2016;Tengberg et al, 2016;Yu et al, 2016), South Africa (Russell and Ward, 2016) and South America (Ochoa-Cueva et al, 2015;Trabaquini et al, 2015). To this point scientific research has mainly focused on the impact of abandonment from the pedological (Giménez-Morera et al, 2010;Brevik, 2013;Bruun et al, 2015;Colazo and Buschiazzo, 2015), hydrological (Keesstra, 2007;Keesstra et al, 2009;Nadal-Romero et al, 2011;Serrano-Muela et al, 2015;Sanjuán et al, 2016), biological (Russell and Ward, 2016;van Hall et al, 2016), geomorphological (Nadal-Romero et al, 2015), and landscape (Lasanta et al, 2015a(Lasanta et al, , 2015b) points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Because cushion plants act as wind shelters and affect sediment movement patterns (Boelhouwers et al, 2000;Haussmann et al, 2009), they could potentially provide 'safe sites' for seed reserve in soil within and adjacent to cushions. The soil seed distribution in the different locations around the cushions can also be used as a tracer of the seed redistribution (Cerdà & García-Fayos, 2002;De Vlaeminck et al, 2005;Yu et al, 2016) and help to understand the seed behaviour (Wang et al, 2016a). Moreover, understanding the fate of the seeds along the slopes is definitive to plan restoration and rehabilitation programmes (Feng et al, 2015;Gilardelli et al, 2016;Qian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%